2011
DOI: 10.1200/jco.2010.32.1711
|View full text |Cite
|
Sign up to set email alerts
|

Donor Lymphocyte Infusions Modulate Relapse Risk in Mixed Chimeras and Induce Durable Salvage in Relapsed Patients After T-Cell–Depleted Allogeneic Transplantation for Hodgkin's Lymphoma

Abstract: These data demonstrate the potential for allogeneic immunotherapy with donor lymphocytes both to reduce relapse risk and to induce durable antitumor responses in patients with Hodgkin's lymphoma after hematopoietic stem-cell transplantation that incorporates in vivo T-cell depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 32 publications
1
90
0
1
Order By: Relevance
“…9 Two studies have demonstrated this effect. 27,28 In our study, among the 30 patients for whom response information was available, the response rate was 27%.…”
Section: Discussionmentioning
confidence: 99%
“…9 Two studies have demonstrated this effect. 27,28 In our study, among the 30 patients for whom response information was available, the response rate was 27%.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrated responses to donor lymphocyte infusion (DLI) and a trend toward a lower relapse rate after allogeneic SCT than after ASCT, especially when chronic graft-versus-host disease (GVHD) occurs, are direct and indirect arguments for a GVHL effect. [37][38][39] Because of the negative aspect of treatment-related mortality (TRM) of myeloablative conditioning regimens, reduced intensity conditioning (RIC) regimens have emerged as a potential option with acceptable TRM and long-term response. 40,41 Importantly, several studies have shown that chemosensitivity at transplantation remains a major predictor of outcome of RIC allogeneic SCT (RIC-allo).…”
Section: Allogeneic Stem-cell Transplantationmentioning
confidence: 99%
“…5,6 Nevertheless, a substantial number of patients will also relapse after HDC and will require further therapy. In this setting, an allo-SCT folllowing reduced intensity conditioning or nonmyeloablative regimens (NMA) has been shown to be feasible [6][7][8][9][10][11][12][13][14] and superior in terms of survival and PFS, when compared with other therapeutic options. 15 The problem with an allo-SCT is that the majority of patients lack an identical sibling and no more than 50% of patients, searching the Registries for unrelated donors or cord blood units, undergo an allo-SCT (World Marrow Donor Association data, 2012 unpublished).…”
Section: Introductionmentioning
confidence: 99%